(3eaJGM GdYdhes - (3GdScGcj GdNhGQRej GdMfaj, CHh jYbhH, SQGL GdOjf, jhSa Hf CHj HcQ Hf eMeO Hf Ydj, J (B626 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B.. (3aEf fhY GdCOH fhY jJaGhJ cKQI TYH hbdI hUYhHI afhf hSghdI hJHGYO WQajf hJOGfjG (B.. (3ef SGFQ GdYdhe ceGdG hfbUGfG hcaGA efRdI gfgGdc (B..s
(3BNQgG (B:s
.. (3hjLQj dPdc GdbQBf eLQi GdMGd Yf GdTYQ ajbGd HfG Ydi ebJVi GdHdGZI heG YdefGg GdTYQ hYdi gPG (B.. (3cja jdRe TjFG eeG PcQJe (B.. (3Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8\222s
(3cTa GdXfhf (B2\1762s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdHdGZIs